Enhancing the water splitting performance via decorating Co3O4 nanoarrays with ruthenium doping and phosphorization. Issue 45 (21st July 2020) - Niu, Jiaqi; Yang, Jian; Channa, Ali Imran; Ashalley, Eric; Yang, Jiachao; Jiang, Jie; Li, Handong; Ji, Haining; Niu, Xiaobin
Abstract : CoRuPO/NF shows low overpotentials in HER and OER. Abstract : Hydrogen is the most promising renewable energy source to replace traditional fossil fuels for its ultrahigh energy density, abundance and environmental friendliness. Generating hydrogen by water splitting with highly efficient electrocatalysts is a feasible route to meet current and future energy demand. Herein, the effects of Ru doping and phosphorization treatment on Co3 O4 nanoarrays for water splitting are systemically investigated. The results show that a small amount of phosphorus can accelerate hydrogen evolution reaction (HER) and the trace of Ru dopant can significantly enhance the catalytic activities for HER and oxygen evolution reaction (OER). Ru-doped cobalt phosphorous oxide/nickel foam (CoRuPO/NF) nanoarrays exhibit highly efficient catalytic performance with an overpotential of 26 mV at 10 mA cm −2 for HER and 342 mV at 50 mA cm −2 for OER in 1 M KOH solution, indicating superior water splitting performance. Furthermore, the CoRuPO/NF also exhibits eminent and durable activities for alkaline seawater electrolysis. This work significantly advances the development of seawater splitting for hydrogen generation.